Defiance. - Tec, Nechama (Oxford University Press, USA, 2008)
The prevailing image of European Jews during the Holocaust is one of helpless victims, but in fact many Jews struggled against the terrors of the Third Reich. In Defiance, Nechama Tec offers a riveting history of one such group, a forest community in western Belorussia that would number more than 1,200 Jews by 1944--the largest armed rescue operation of Jews by Jews in World War II. Tec reveals that this extraordinary community included both men and women, some with weapons, but mostly unarmed, ranging from infants to the elderly. She reconstructs for the first time the amazing details of how.